Outcomes of cats treated with maxillectomy: 60 cases. A Veterinary Society of Surgical Oncology retrospective study. (16th August 2020) - Liptak, Julius M.; Thatcher, Graham P.; Mestrinho, Lisa A.; Séguin, Bernard; Vernier, Timothy; Martano, Marina; Husbands, Brian D.; Veytsman, Stan; van Nimwegen, Sebastiaan A.; De Mello Souza, Carlos H.; Mullins, Ronan A.; Barry, Sabrina L.; et al.
Abstract: Maxillectomy is poorly described for the management of oral tumours in cats and is occasionally not recommended because of the high complication rate and sub‐optimal outcome reported in cats treated with mandibulectomy. The purpose of this study was to retrospectively evaluate the complications and oncologic outcome in cats treated with maxillectomy. Sixty cats were included in the study. Maxillectomy procedures included unilateral rostral (20.0%), bilateral rostral (23.3%), segmental (10.0%), caudal (20.0%) and total unilateral maxillectomy (26.7%). Intra‐operative and post‐operative complications were reported in 10 (16.7%) and 34 (56.7%) cats, respectively. The most common post‐operative complications were hyporexia (20.0%) and incisional dehiscence (20.0%). The median duration of hyporexia was 7 days. Benign tumours were diagnosed in 19 cats (31.7%) and malignant tumours in 41 cats (68.3%). Local recurrence and metastatic rates were 18.3% and 4.9%, respectively; the median progression‐free interval (PFI) was not reached. The disease‐related median survival time was not reached overall or for either benign or malignant tumours. The 1‐ and 2‐year survival rates were, respectively, 100% and 79% for cats with benign tumours, 89% and 89% for cats with malignant tumours, 94% and 94% for cats with fibrosarcomas, 83% and 83% for cats with squamous cell carcinomas, and 80% and 80% for cats with osteosarcomas. Poor prognostic factors included mitotic index for PFI, adjuvant chemotherapy for both PFI and survival time, and local recurrence for survival time. Maxillectomy is a viable treatment option for cats resulting in good local tumour control and long survival times.